2006
DOI: 10.1016/j.neulet.2006.01.025
|View full text |Cite
|
Sign up to set email alerts
|

A portable and low-cost fMRI compatible pneumatic system for the investigation of the somatosensensory system in clinical and research environments

Abstract: There still is a need for devices that allow reproducible stimulation of skin areas of the human body. We constructed a stimulation system and tested it by using brief pneumatic stimulation to the right thumb of nine healthy volunteers. BOLD-signals in response to tactile stimulation with frequencies of 1, 3 and 5 Hz were measured using a 3 T MRI scanner. The stimulation device consists of synthetic membranes connected to plastic tubes capable of carrying compressed air, and an electronic component, which cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 19 publications
2
33
0
Order By: Relevance
“…We choose pneumatic stimulation as it has been shown that this form of fingertip stimulation activates the human primary sensory cortex (Elbert et al, 1995; Candia et al, 2003), while electrical stimulation activates afferent fibers (Hashimoto et al, 2004). Stimulation was conducted as described by Wienbruch and colleagues (2006). Non-painful stimuli of 50 ms duration, with a frequency of 1.5 Hz were applied to finger clips with flexible membranes placed on each finger segment of d2 and d5.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…We choose pneumatic stimulation as it has been shown that this form of fingertip stimulation activates the human primary sensory cortex (Elbert et al, 1995; Candia et al, 2003), while electrical stimulation activates afferent fibers (Hashimoto et al, 2004). Stimulation was conducted as described by Wienbruch and colleagues (2006). Non-painful stimuli of 50 ms duration, with a frequency of 1.5 Hz were applied to finger clips with flexible membranes placed on each finger segment of d2 and d5.…”
Section: Methodsmentioning
confidence: 99%
“…The incoming airflow drives a circular synthetic membrane of approximately 0.8 cm 2 (4D Neuroimaging Inc., San Diego, USA) through plastic standard tubes (PUN-4×0,75-SI; outside diameter 4 mm, inside diameter 2.6 mm and PUN-3×0,5-SI; outside diameter 3 mm, inside diameter 2.1 mm; copper and Teflon-free for QS push-in fittings, Festo®) [cf. (Wienbruch et al, 2006)]. During measurements subjects were instructed to concentrate on the stimulus.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The study subjects were asked to lie still with their eyes closed and the head was stabilised with cushions and foam pads during the experiment. The stimuli system was pneumatically driven and electronically controlled, based on the same principle as that presented by Wienbruch et al. (2006).…”
Section: Methodsmentioning
confidence: 99%
“…Higher stimulation frequencies can be achieved by using nonmagnetic valves, suited for operation inside the MR scanner room. Multi-channel stimulation designs are feasible with multiple valves and pickups (Wienbruch et al, 2006). Pneumatic devices have shown to cause somatosensory brain activation, but failed to additionally activate motor cortical areas in somatosensory paradigms.…”
Section: Principles and Technical Designsmentioning
confidence: 99%